Aneurysm and Neurocysticercosis: Casual or Causal Relationship? Case Report and Review of the Literature. (30th October 2011) - Agapejev, Svetlana; Parra-Marinello, João Luiz; Bazan, Rodrigo; Ueda, Anete Kinumi; Zanini, Marco Antonio
Abstract : Four cases of suggestive inflammatory aneurysms in patients with neurocysticercosis have been described. We report a case of a 49-year-old woman who presented with subarachnoid haemorrhage from a right middle cerebral artery bifurcation aneurysm and had a casual relationship with neurocysticercosis. At surgery, a viable cysticercus without signs of inflammation or thickened leptomeninges was found in the distal position of the aneurysm. Postoperatively, the patient received albendazole and dextrochlorpheniramine. In the subsequent three years, the patient was asymptomatic and took drugs to prevent convulsion and arterial hypertension. The relationship between NCC and the presence of cerebral aneurysm is discussed.